PENERAPAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATERI SATUAN BAKU DAN TIDAK BAKU DI KELAS IV SD - Surya Putri Alfi Sari; Ageng Triyono; Nurhidayati (STKIP Subang, 2026)
This classroom action research aims to: (1) describe the application of the Jigsaw learning model; (2) improve student activeness; and (3) improve student learning outcomes on the topic of Standard and Non-Standard Units in grade IV. The re-search consisted of two cycles, each with planning, action, observation, and reflec-tion stages. The subjects were 27 fourth-grade students. Instruments included ob-servation sheets, questionnaires, and multiple-choice tests. The Jigsaw model was implemented through the formation of home groups and expert groups. Pre-cycle data showed student activeness at 36% (very poor category) and learning mastery at 37.05%. In cycle I, activeness increased to 72% (active category) and learning mastery to 59.26%. In cycle II, activeness increased significantly to 90% (very ac-tive category) and learning mastery to 85.19%, exceeding the target of ≥75%. The conclusion is that the application of the Jigsaw learning model can improve the ac-tiveness and learning outcomes of fourth-grade students.